High normal albuminuria is independently associated with aortic stiffness in patients with Type 2 diabetes. Issue 10 (23rd April 2014) - Liu, J.‐J.; Tavintharan, S.; Yeoh, L. Y.; Sum, C. F.; Ng, X. W.; Pek, S. L. T.; Lee, S. B. M.; Tang, W. E.; Lim, S. C.; the SMART2D study
Abstract Background High normal albuminuria is associated with higher cardiovascular risk in patients with diabetes. Increased aortic stiffness is an established risk factor of vascular events. However, the relationship between albuminuria within the normal range (0–30 mg/g) and aortic stiffness in patients with Type 2 diabetes is unknown. Methods A total of 614 normoalbuminuric subjects with Type 2 diabetes with spot urinary albumin:creatinine ratio ≤ 30 mg/g and estimated glomerular filtration rate ≥ 60 ml min−1 1.73 m−2 were included in the study. Aortic stiffness was assessed by carotid–femoral pulse wave velocity. Results Pulse wave velocity increased progressively with the increase of albumin:creatinine ratio within the normoalbuminuric range (0–30 mg/g). Only 2.6% of the subjects with an albumin:creatinine ratio in the lowest quartile (0.7–3.4 mg/g) were classified as having aortic stiffness (pulse wave velocity ≥12 m/s). In contrast, the proportion of subjects with aortic stiffness increased significantly with the increase of albumin:creatinine ratio level (11.0%, 10.4% and 13.6% in albumin:creatinine ratio quartiles 2, 3 and 4, respectively, P = 0.008). A logistic regression model revealed that the odds of having aortic stiffness were increased by 56% with a 1‐sd increase of log albumin:creatinine ratio after adjustment for age, gender, duration of diabetes, HbA1c, blood pressure, HDL and LDL cholesterol, estimated glomerular filtration rate, BMI, usage of renin–angiotensin system antagonists, statins and insulin. Conclusions High normal albuminuria is associated with aortic stiffness in patients with Type 2 diabetes, which may in part explain their increased cardiovascular risk.